AB0303 Ultrasound aspect of posterior tibial tendon in rheumatoid arthritis. (12th June 2018) - Afilal, S.; rkain, H.; fellous, S.; tahiri, L.; alami, N.; Guieu, R.; Jammes, Y.; Allali, F.; Hajjaj-Hassouni, N.
Abstract : Background: Posterior tibial tendon involvement is common in rheumatoid arthritis. Ultrasound has an important place in the examination of this tendon. Objectives: Evaluate the prevalence of ultrasound signs of posterior tibial tendon involvement in rhumatoid arthritis. Methods: This is a cross-sectional study that included fourteen consecutive patients (100% female, mean age 55.3 years) with rhumatoid arthritis (median duration of progression of 13.5 years, mean specialised care of 2.1 years). A grey and Doppler ultrasound study was performed on affected feet, looking for effusion, thickening or corporal thinning, hypoechoic aspect, fissures, and Doppler activity in the posterior tibial tendon. Results: 28 feet were studied with ultrasound evaluation of the posterior tibial tendon. Figure 1 illustrates the prevalence of the pathological aspects of the posterior tibial found on ultrasound examination. Conclusions: This study illustrates the different pathological aspects of the posterior tibial tendon. It highlights the high prevalence of this tendinopathy in the rheumatoid foot. Ultrasound allows accurate assessment of this tendon in RA patients. A large-scale study compared with a control group is necessary to better interpret and complete these preliminary results. Disclosure of Interest: None declared